BOLAJAQ MUZÍKA MÁDENIYATÍ PÁNI OQÍTÍWSHÍLARÍNA SAZ ÁSPABLARÍN SHERTIWDI ÚYRETIWDIŃ ZÁRÚRLIGI HÁM ÁHMIYETI - Tajetdinova, S.M. (SCIENCE and SOCIETY, 2024)
This article examines the improtance of teaching playing musical instruments to future teachers of music culture to fulfil the needs of modern education.